1929
DOI: 10.1017/s0021859600011229
|View full text |Cite
|
Sign up to set email alerts
|

A study of the metabolism of two breeds of pig: (With some remarks on a third)

Abstract: The metabolism of a Berkshire and a Middle White pig has been investigated by means of the calorimeters at the School of Agriculture, Cambridge. The general routine and technique of the observations have been as heretofore.Measurements of the fasting katabolism of each of the two pigs have been obtained in a series extending from an early age to maturity, and the phenomena in general follow the lines of those originally discovered in the Large White; but the fasting katabolism of the Middle White was below tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1932
1932
1981
1981

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Graham et al (1959) found the corresponding temperature for single shorn sheep to be 23°C. Although a narrow range of temperature was not studied in this region the assumption agrees with previous reports on the critical temperature of pigs (Tangl, 1912;Capstick and Wood, 1922;Deighton, 1929;Heitman and Hughes, 1949). Although a narrow range of temperature was not studied in this region the assumption agrees with previous reports on the critical temperature of pigs (Tangl, 1912;Capstick and Wood, 1922;Deighton, 1929;Heitman and Hughes, 1949).…”
Section: Resultssupporting
confidence: 89%
“…Graham et al (1959) found the corresponding temperature for single shorn sheep to be 23°C. Although a narrow range of temperature was not studied in this region the assumption agrees with previous reports on the critical temperature of pigs (Tangl, 1912;Capstick and Wood, 1922;Deighton, 1929;Heitman and Hughes, 1949). Although a narrow range of temperature was not studied in this region the assumption agrees with previous reports on the critical temperature of pigs (Tangl, 1912;Capstick and Wood, 1922;Deighton, 1929;Heitman and Hughes, 1949).…”
Section: Resultssupporting
confidence: 89%
“…Deighton (1929) found that the same figure fitted his observations on the Berkshire pig but that the critical temperature of the Middle White was around 16° C. Below these critica 1 temperatures-that is, at temperatures quite common in our byres-the metabolism, and therefore the food requirement of the animals, is increased. Deighton (1929) noted that at the critical temperature the fasting metabolism of the pig was higher than that of better insulated animals with the same kind of gastro-intestinal tract: 37 calories per square metre per hour for the pig against 34-5 for man, 34-4 for the dog and 32-4 for the rabbit. Wallach, Newland & McMillen (1948) found a sharp fall of 3-9° F. in the body temperature of baby pigs at birth followed by a gradual rise to normal at about 2 days of age.…”
Section: Discussionsupporting
confidence: 58%
“…For the purposes of comparison a number of results have been collected (Table 4) in which the measurements were made at least 48 h after the last feed. Deighton (1923Deighton ( , 1929 and Capstick & Wood (1922) measured the heat loss for the animals only when they were asleep and not throughout the 24 h period. Their values have been converted to a mean 24 h rate by multiplying by IOO + 83, since it has been found in the present study that the heat loss during the period 00.00-09.00 hours was 83 yo of that determined as the mean 24 h rate (see Fig.…”
mentioning
confidence: 99%